Langzeitpflege in der digitalen Gesundheitsökonomie - Mayert, Andreas (Nomos Verlagsgesellschaft mbH & Co. KG, 2026)
To date, an in-depth empirical look into the reasons for the slow digitalization of small to medium-sized long-term care providers in suburban areas has been lacking. This book closes this research gap by conducting a qualitative empirical study and an extensive secondary data analysis. From working conditions and staff shortages in the care sector, the economic conditions of long-term care services and facilities to the potential of digital technologies and the difficulties of their implementation, social economist Andreas Mayert leaves no question unanswered. The publication is aimed at care providers and their associations, those responsible for long-term care policy and, last but not least, researchers in the field of long-term care. This title is also available as open access.